Peran Guru dalam Mengembangkan Gerakan Literasi Melalui Kegiatan Kunjungan Perpustakaan di Sekolah Dasar - Riska Fitriani; Piya Pitriyani (Journal of Basic Education Research, 2023)
Purpose of the study: This study aims to describe the role of the teacher in developing the school literacy movement through library visiting activities in class II in Elementary School 112 Perumnas. Methodology: Research data was obtained with a qualitative approach. A qualitative approach uses observation, interviews, and documentation with residents of Elementary School 112/I Perumnas, namely class II teachers, librarian teachers, and students. After the data is obtained, the data is analyzed using the Miles and Hubberman technique through data reduction, data presentation, and concluding. Main Findings: The results of this study indicate that the teacher's role is to provide facilities and infrastructure to support literacy activities, the teacher and students carry out literacy activities regularly, the teacher invites students to carry out literacy activities by visiting the library, guides students in carrying out literacy activities, and helps students who experience difficulties. Novelty/Originality of this study: From the results of this study, it is suggested that teachers can overcome the obstacles that occur in literacy activities in class and library visiting literacy activities, and teachers must also pay attention to their students in carrying out literacy activities so that they run well.